Restrained and External-Emotional Eating Patterns in Young Overweight Children–Results of the Ulm Birth Cohort Study - Hirsch, Oliver (Public Library of Science, 2014)
Childhood obesity is one of the greatest public health challenges in Western countries. Abnormal eating behavior is thought to be a developmental trajectory to obesity. The Eating Pattern Inventory for Children (EPI-C) has not been used for children as young as eight years, and possible associations with body weight have not yet been established. Five hundred and twenty-one children of the Ulm Birth Cohort Study (UBCS; age eight) filled out the EPI-C and BMI was assessed. Adequacy of the scales was tested with confirmatory factor analysis and a MANOVA and cluster analysis established associations between eating patterns and BMI. The factor structure of the EPI-C was confirmed (GFI = .968) and abnormal eating behavior was associated with overweight (χ(2)(8) = 79.29, p<.001). The EPI-C is a valid assessment tool in this young age group. Overweight children consciously restrain their eating.